analisis kadar analisis kadar senyawa tanin pada teh daun tanaman kakao (theobroma cacao L.) secara spektrofotometri UV-Vis - arifin, nurrizky afiah; Suhaenah, Asriani; Maryam, St. (PHARMACY UMI JOURNAL SYSTEM, 2024)
Cocoa leaves (Theobroma cacao L.) contain secondary metabolite compounds, namely flavonoids, saponins, tannins, theobromine, caffeine, anthocyanins, leucoanthocyanins and catechol. This research aims to determine the levels of tannin compounds contained in tea preparations from the leaves of the cocoa plant (Theobroma cacao L.) based on a comparison of growing places, namely Wajo, Jeneponto and Malino. The research was carried out qualitatively using wet reagents and quantitatively using the UV-Vis spectrophotometric method. Based on the qualitative test results, FeCl3 1% reagent produces a green solution blackish, the gelatin test produces precipitation, while the potassium ferricyanide and ammonia reagent produces a dark brown color, these results indicate that cocoa leaves contain tannin compounds, for the quantitative test it is measured using UVVis spectrophotometry at a maximum wavelength of 772 nm with a reference, namely gallic acid. . The results obtained for the Wajo area were 1,618mgGAE/g, Jeneponto 2,334mgGAE/g, and Malino 1,030mgGAE/g, based on these data it can be concluded that cocoa leaves contain tannin compounds and the highest levels are in the Jeneponto area.